2011
DOI: 10.1007/s11832-010-0304-4
|View full text |Cite
|
Sign up to set email alerts
|

Use of a “kickstand” modification for external fixation of lower extremity fractures in children

Abstract: Purpose To evaluate and describe the kickstand modification and its use in children with lower extremity fractures. Methods Retrospective review identified eight children in whom the kickstand technique was used during treatment of their lower extremity fractures. The seven boys and one girl had a mean age of 11.8 years. All fractures were caused by high-energy trauma. Five of the eight tibial fractures were open fractures (one type 1, one type 2, and three type 3B), and five of the eight patients had multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…The rod at the level of the metatarsal head prevents the development of equinus contracture, which is not done in the method by Castro-Aragorn 2 et al or Sawyer et al 7 and Berkowitz 1 et al…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rod at the level of the metatarsal head prevents the development of equinus contracture, which is not done in the method by Castro-Aragorn 2 et al or Sawyer et al 7 and Berkowitz 1 et al…”
Section: Discussionmentioning
confidence: 99%
“…This decreases pain, discomfort, and overall morbidity. This is unlike the method described by Budford et al 6 The rod at the level of the metatarsal head prevents the development of equinus contracture, which is not done in the method by Castro-Aragorn 2 et al or Sawyer et al 7 and Berkowitz 1 et al…”
Section: The Frame Cannot Be Assembled In Patients Who Have a Ring Fimentioning
confidence: 97%
“…Kickstand application techniques using 2 vertical bars attached to either side of the hindfoot, 2 angled V-bars attached to 2 L-bars, and more complex 3-plane bar constructs have been described. 1,3,4,9 Only 1 previous study has described the use of a circular external fixation technique, with mention of the use of a half-ring for temporary intraoperative elevation to facilitate assembly of more distal pins and wires. 5 Use of a thin-wire ring construct affords several advantages to traditional external fixator kickstands.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated the ease and effectiveness of adding additional bars to the external fixator construct, "kickstands," to prevent heel ulcers. 1,3,9 Other fields of medicine have also taken advantage of adjuvant external fixation in the management of lower extremity reconstructive procedures. More specifically, previous studies have described the use of external fixation to constrain joints and alleviate flap compression to protect flap coverage.…”
mentioning
confidence: 99%
“…The use of external fixation can yield excellent stability to allow the vascular repair to be performed in a controlled environment to protect the completed vascular repair from disruption [ 5 ]. Nevertheless, the current research paid more attention to the complex lower extremity deformity correction [ 6 9 ], the modification for external fixation [ 10 12 ] or case report of the use of external fixators in fractures [ 11 ]. However, according to our knowledge, to date, there has been no published work regarding the outcome of the treatment of external fixators in lower extremity arterial injuries.…”
Section: Introductionmentioning
confidence: 99%